Trackline detection probability of Antarctic minke whales: analyses of the BT mode experiments conducted on the IWC-SOWER cruises 2005/06–2007/08 - Burt, M. Louise; Borchers, David L.; Ensor, Paul (J. Cetacean Res. Manage., 2023)
IWC sightings surveys to obtain abundance estimates of cetaceans have taken place in the Antarctic since 1978/79. In order to interpret the minke whale abundance from these surveys and trial different search protocols for future cruises, Buckland-Turnock (BT) search mode experiments were conducted during the IWC-SOWER 2005/06, 2006/07 and 2007/08 cruises. BT search mode is a particular configuration of a double-observer survey and two configurations of BT mode were implemented on the SOWER cruises; BT-NSP mode and BT-option 2. Normal standard passing (NSP) mode is a standard search mode for SOWER vessels and in BT-NSP mode, the observer located on the barrel became the primary and searched as usual in NSP mode with 7×50 binoculars; the observers on the upper bridge became the tracker and used big eye binoculars mounted on the upper bridge. Thus, the probability of detection for the observer in the barrel can be estimated which can help inform interpretations of abundance estimates of SOWER data. For BT-NSP mode, the estimates of detection probability on the trackline for the observer in the barrel ranged between 0.35 (CV = 0.57) to 0.69 (CV = 0.23) for the different years and combinations of data and models. In BT-option 2, the observer on the barrel (searching with 7×50 binoculars) acted as tracker and the observer on the independent observer (IO) platform acted as the primary (searching with naked eye). For this configuration, the estimates of primary detection probability on the trackline were 0.25 (CV = 0.59) and 0.28 (CV = 0.50) for two different models.